Contribution of plastic waste recovery to greenhouse gas (GHG) savings in Spain. (December 2015) - Sevigné-Itoiz, Eva; Gasol, Carles M.; Rieradevall, Joan; Gabarrell, Xavier
Highlights: We determine the GHG emissions of plastic waste recovery in Spain. We evaluate quality and market of plastic waste and application of plastic recycled. We conduct dynamic material flow analysis and life cycle assessment. The highest GHG emissions savings are obtained for mechanical recycling. Export and low quality of plastic waste reduce the GHG emissions savings. Abstract: This paper concentrates on the quantification of greenhouse gas (GHG) emissions of post-consumer plastic waste recovery (material or energy) by considering the influence of the plastic waste quality (high or low), the recycled plastic applications (virgin plastic substitution or non-plastic substitution) and the markets of recovered plastic (regional or global). The aim is to quantify the environmental consequences of different alternatives in order to evaluate opportunities and limitations to select the best and most feasible plastic waste recovery option to decrease the GHG emissions. The methodologies of material flow analysis (MFA) for a time period of thirteen years and consequential life cycle assessment (CLCA) have been integrated. The study focuses on Spain as a representative country for Europe. The results show that to improve resource efficiency and avoid more GHG emissions, the options for plastic waste management are dependent on the quality of the recovered plastic. The results also show that there is an increasing trend of exporting plastic waste for recycling, mainly to China, that reduces the GHG benefits from recycling, suggesting that a new focus should be introduced to take into account the split between local recycling and exporting.